CATATAN NIKAH MENURUT PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Iqbal, Muhammad (Jurnal Mentari, 2011)
Marriage has a vital value in personal life, family and social life. The act No.1, 1974 about marriage and its various directions for use, requires all citizen to register their marriage at a legal institution (The office of religious affair) in order to have legal force. However, Islamic law does not require the registration of marriage because, in Islamic law it is more important to fulfill the obligatory rules of marriage it self. The discussion in this writing aims to explore the position of marriage registration in Islamic Law Perspective and Positive Law in Indonesia. Key words: marriage registration, legal force women and children protection.     DAFTAR  PUSTAKA Buku Hamid Sarong, 2010, Hukum Perkawinan Islam di Indonesia, Yayasan Pena, Banda Aceh.Mukti Arto, 1996, Masalah Pencatatan Perkawinan dan Sahnya Perkawinan, Mimbar     Hukum No.26 TahunVII, Jakarta. Ahmad Rafiq, 1998, Hukum Islam di Indonesia, Rajawali Pers, Jakarta. Amiur Nuruddin dan Azhari Akmal Tarigan, 2006, Hukum Perdata Islam di Indonesia, Kencana,   Jakarta. Ainur Rafiq (ed), 2002, Menggagas Paradigma Ushul Fiqih Kontemporer, Ar-Ruzz, Yogyakarta. M. Atho Mudzhar, 1998, Membaca Gelombang Ijtihad Antara Tradisi dan Liberasi, Titian ilahi Pers, Jakarta. M. Yahya Harahap, 1975, Hukum Perkawinan Nasional, Cet. I, Zahir Trading, Medan.   Peraturan Perundang-Undangan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan. Peraturan Pemerintah Nomor 9 Tahun 1975 tentang Pelaksanaan Undang-Undang  Nomor 1 Tahun 1974 Tentang  Perkawinan. Inpres Nomor 1 Tahun 1991 Tentang Kompilasi Hukum Islam.